Analisis Efektivitas Implementasi Digital Learning pada Masa Pandemik Covid-19 - Paula Dewanti; Ni Putu Linda Santiari; Kadek Vishnu Vedamurthi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
This study is a continuation of previous research conducted by researchers on theimplementation of Digital Learning in several countries as an Emergency Response to theexceptional circumstances of the Covid-19 pandemic, considering the most recent developmentsof virus variants, the increasing number of virus exposures, and the uncertainty of the pandemic'send date. In this study, researchers compared the use of Digital Learning in Indonesianuniversities. This follow-up study was conducted to identify best practices, such as StudentEngagement and Student Experience, that are expected to add more value to the current ELearningimplementation. This aspect should be explored in order to determine whether DigitalLearning through E-Learning is a strategic move that will result in better learning outcomes atIndonesian universities. In the research approach, a comparative study is used, in which data isobtained from reliable resources relevant to the subject of study, namely contact persons viacorrespondence. Other data from respondents is used to quantify the impact of virtual learningduring the ongoing Covid-19 pandemic using a Likert Scale. Respondents to this study'seffectiveness survey were students of the lecturers who were the subject of the research.